The Effect of Thermochemical Sulphate Reduction on the Carbon Isotope Ratio of Individual Light Hydrocarbons Associated With Natural Gas - Hu, Guoyi; Guo, Jinhao; Tian, Lianjie; Wu, Xiaoqi; Su, Jin; Li, Zhisheng; Fang, Chenchen (Frontiers in Earth Science, 2022)
To understand the effect of thermochemical sulphate reduction (TSR) on the stable carbon isotopes of light hydrocarbons (LHs) associated with natural gas, 15 gases with varying H2S content from Ordovician reservoir of the Tazhong gas field (TZ-I) in Tarim Basin and Triassic Leichoupo formation reservoir of the Zhongba gas field (ZB) in Sichuan Basin were collected. The components and stable carbon isotope ratios of the C1-C4 alongside the individual LHs (C6-C7) in these gases were analysed. The origin of natural gas and the effect of TSR on the stable carbon isotope ratio of individual LHs in natural gas were studied. The data from the δ13C2 values and LHs indicated that the gases were oil-associated gases. Moreover, the gas sourness index demonstrated that the gases from the TZ-I and ZB gas fields were in the early liquid carrier-involved and heavy-hydrocarbon gas-dominated TSR stages, respectively. The comparison of stable carbon isotope ratios of the LHs between the two gas fields revealed that TSR exhibited a complex effect on the stable carbon isotope ratios of LHs, but only little effect on 2-methylpentane (2-MP) and 3-methylpentane (3-MP). The δ13C values of benzene (BEN) and toluene (TOL) were 28.6‰ and 29.4‰ in the TZ-I and -27.7‰ and -28.1‰ in the ZB gas field. The stable carbon isotope ratios of BEN and TOL exhibited positive trends, likely driven by TSR. Meanwhile, TSR was isotopically heavier, with a small trend in the δ13C values for cycloalkanes such as methyl cyclopentane (MCP), cyclohexane (CH), and methylcyclohexane (MCH). Therefore, the influence of TSR on the carbon isotopes of individual LHs should be considered while using the stable carbon isotope ratio of cycloalkanes, BEN, and TOL. This is required to identify the genetic type and source of marine natural gas, especially at the cut-off point (δ 13C=-24‰) of coal-derived gas and oil-associated gas.